Use of oxytocin during Caesarean section at Princess Marina Hospital, Botswana: An audit of clinical practice - Billy M. Tsima; Bob Mash; Farai D. Madzimbamuto (AOSIS, 2013)
Background: Oxytocin is widely used for the prevention of postpartum haemorrhage. In the setting of Caesarean section (CS), the dosage and mode of administrating oxytocin differs according to different guidelines. Inappropriate oxytocin doses have been identified ascontributory to some cases of maternal deaths. The main aim of this study was to audit the current standard of clinical practice with regard to the use of oxytocin during CS at a referral hospital in Botswana.Methods: A clinical audit of pregnant women having CS and given oxytocin at the time of the operation was conducted over a period of three months. Data included indications for CS, oxytocin dose regimen, prescribing clinician's designation, type of anaesthesia for the CS and estimated blood loss.Results: A total of 139 case records were included. The commonest dose was 20 IU infusion (31.7%). The potentially dangerous regimen of 10 IU intravenous bolus of oxytocin was used in 12.9% of CS. Further doses were utilized in 57 patients (41%). The top three indications forCS were fetal distress (36 patients, 24.5%), dystocia (32 patients, 21.8%) and a previous CS (25 patients, 17.0%). Estimated blood loss ranged from 50 mL - 2000 mL.Conclusion: The use of oxytocin during CS in the local setting does not follow recommended practice. This has potentially harmful consequences. Education and guidance through evidencebased national guidelines could help alleviate the problem.